Monday

December 22, 2014

December 22, 2014

Posted by **JB** on Tuesday, January 3, 2012 at 9:13pm.

f(x)=6/(1-x)

g(x)=(1-6/x)

- College Algebra -
**Steve**, Wednesday, January 4, 2012 at 10:39amwhat's the problem? Just plug and chug:

f(g) = ln(g-1) = ln(1+e^x-1) = ln(e^x) = x

g(f) = 1+e^f = 1 + e^(ln (x-1)) = 1 + x-1 = x

Just keep in mind the definition of a logarithm:

e^lnx = x

ln e^x = x

**Answer this Question**

**Related Questions**

College Algebra - Verify that the function f and g, are inverses of each other ...

algebra - Verify that the functions f and g are inverses of each other by ...

Precalculus - Verify that the functions f and g, are inverses of each other by ...

pre calculus - verify functions f and g are inverses of each other by showing ...

precalculus - verify the functions are inverses of each other by showing that f(...

College Algebra - verify that the functions of f and g are inverse of each other...

College Algebra! help! - Consider the following functions f(x)= (7x+8)/(x+3) and...

Algebra - Graph and label the following two functions: f(x)=(x^2+7x+12)/(x+4) g(...

algebra II - How do you verify inverses? the question is y=3x-3... we know how ...

math-please I really need help!!!!! - Consider the functions f(x)=2x+8/x+6; g(x...